Komparasi Kepemimpinan Presiden Sby Dan Jokowi Dalam Mitigasi Amdal Di Indonesia - Faried, Ade; Marzaniar, Putri; Nurzalikha, Siti (UIR Press, 2025)
This study compares the environmental policy and implementation of Environmental Impact Assessment (AMDAL) during the administrations of President Susilo Bambang Yudhoyono (SBY) and President Joko Widodo (Jokowi). Under SBY, environmental protection was emphasized through strict regulations such as Law No. 32 of 2009 and the forest moratorium policy, aiming to balance development with ecological preservation. However, weak law enforcement and limited public participation reduced its effectiveness. In contrast, Jokowi’s administration introduced the Omnibus Law (Law No. 11 of 2020 on Job Creation), reforming environmental licensing through a risk-based approach to accelerate investment, though raising concerns about weakened environmental oversight. Using a qualitative Systematic Literature Review (SLR) method, this study analyzed 25 academic journals and policy documents published between 2004 and 2024. The results show that while both administrations sought sustainable development, they faced similar challenges, namely weak implementation, low transparency, and limited community involvement. The study concludes that strengthening institutional monitoring and enhancing public participation are essential to ensure AMDAL’s effectiveness as a tool for sustainable development.